Temperature-resistant and yellowing-resistant UV structural adhesive as well as preparation method and application thereof
By using functional acrylate and compound antioxidants, combined with temperature-resistant resin, a temperature-resistant and yellowing-resistant UV structural glue was prepared, which solved the problems of incomplete curing, surface stickiness and yellowing during use, and achieved higher temperature resistance and yellowing resistance.
Patent Information
- Application Number
- CN202510368957.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
AI Technical Summary
Common problems during use of existing UV structural adhesives include whitening after curing, sticky surface, incomplete curing and yellowing, etc., and it is difficult to meet the requirements of temperature and yellowing at the same time.
Functional acrylate and compound antioxidant are used as the main raw materials, and a temperature-resistant UV structural glue that is resistant to heat and yellowing is prepared by combining the main antioxidant and auxiliary antioxidant, combined with temperature-resistant resins such as epoxy acrylate.
It significantly improves the temperature resistance and yellowing resistance of UV structural adhesives, avoids the problems of incomplete curing and surface sticking, and meets the needs of photovoltaic cells for transparency and good weather resistance.
Smart Images

Figure CN119875570A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photovoltaic materials, and in particular to a temperature-resistant and yellowing-resistant UV structural adhesive and a preparation method and application thereof. Background Art
[0002] SMBB (Silver Metallization Between Busbars) technology is a photovoltaic cell module interconnection technology, mainly used in the manufacturing process of photovoltaic cell modules. This technology uses fine silver paste strips instead of traditional main grid silver electrodes to connect multiple battery cells in series to form a module. SMBB technology can improve the power and efficiency of the module while reducing the use of silver paste, thereby reducing costs.
[0003] The 0BB (no main grid) process is a further upgrade of the SMBB technology. It eliminates the main grid and screen-printed fine grid in the metal electrode screen printing process, and optimizes the width and spacing of the secondary grid. In the component stage, the original main grid and the secondary grid are attached to the part to gather current, and the welding strip (wire) is replaced to achieve the interconnection of the battery cells. In addition, the welding strip process is developing in the direction of refinement, and its specifications will be further refined to about 0.2mm. The welding strip is a copper-tin alloy.
[0004] The function of UV structural adhesive is to bond and fix the welding ribbon (wire) to the cell through the printing process. Photovoltaic cells convert light energy into electrical energy. The greater the light absorption of the cell, the higher the electrical energy, so all materials on the cell must be transparent and have good weather resistance. Therefore, the technical requirements for UV structural adhesive are: 1) yellowing resistance; 2) high transmittance; 3) temperature resistance; 4) processability, etc. Several common problems of UV structural adhesive during use include whitening after curing, sticky surface, incomplete curing, yellowing, etc. These problems are usually caused by the generation of tiny bubbles during the curing process of UV glue, insufficient ultraviolet radiation, insufficient curing time, or poor ultraviolet transmittance of the material.
[0005] CN117384580A discloses a high thixotropic, high temperature and yellowing resistant photovoltaic soldering strip UV glue, a preparation method and a gluing method, which improves the temperature resistance of the UV glue by a compound powder, and utilizes the unique rheological properties of the mixed powder to prevent the glue from spreading before curing, thereby avoiding large-scale contamination of the battery cell. However, the physical method has a sedimentation risk, and the yellowing resistance of the UV glue is not described. Summary of the invention
[0006] Problem that the invention aims to solve
[0007] In view of the above problems existing in the prior art, the object of the present invention is to provide a UV structural adhesive with good temperature resistance and yellowing resistance.
[0008] Solutions for solving problems
[0009] The invention provides a heat-resistant and yellowing-resistant UV structural adhesive. The raw materials for preparing the UV structural adhesive include functional acrylate and compound antioxidant, wherein the compound antioxidant includes a main antioxidant and an auxiliary antioxidant.
[0010] Preferably, the mass ratio of the primary antioxidant to the secondary antioxidant is 1:2 to 2:1.
[0011] Preferably, the primary antioxidant is selected from one or more of 1010, 1071, and BHT; Preferably, the secondary antioxidant is selected from one or more of 168, 626.
[0012] Preferably, the mass ratio of the primary antioxidant to the secondary antioxidant is 1:1.
[0013] Preferably, the primary antioxidant is 1010; Preferably, the secondary antioxidant is 168.
[0014] Preferably, the functional acrylate is selected from one or more of epoxy acrylate and multifunctional polyurethane acrylate; Preferably, the epoxy acrylate is CN104 NS and / or CNUVE151 NS; Preferably, the multifunctional polyurethane acrylate is one or more selected from HP6612, HP6617, and HP6400.
[0015] Preferably, the raw materials for preparing the UV structural adhesive further include: UV monomer, photoinitiator, photocuring agent, coupling agent, and gas silicon; Preferably, in parts by weight, the raw materials for preparing the UV structural adhesive include: UV monomer 40~50% Photoinitiator 1~10% Light curing agent 30~40% Functional acrylate 5~15% Compound antioxidant 0.1~1% Coupling agent 0.1~1% Gas silicon 1~5%.
[0016] Preferably, the raw materials for preparing the UV structural adhesive are composed of the following components in parts by weight: UV monomer 45.5% Photoinitiator 4% Light curing agent 35.2% Functional acrylate 11% Compound antioxidant 0.6% Coupling agent 0.5% Gas silicon 3.2%.
[0017] Preferably, the UV monomer is IBOA; Preferably, the photoinitiator is an ultraviolet photoinitiator; Preferably, the photocuring agent is polyurethane acrylate; Preferably, the coupling agent is a siloxane coupling agent; Preferably, the fumed silica is hydrophilic fumed silica.
[0018] Preferably, the UV monomer is SR506; Preferably, the photoinitiator is 184D and TPO; Preferably, the light curing agent is CR91582; Preferably, the coupling agent is A187; Preferably, the gas silicon is A200; Preferably, the raw materials for preparing the UV structural adhesive are composed of the following components in parts by weight: SR506 45.5% 184D 2% TPO 2% CR91582 35.2% HP6612 11% 1010 0.3% 168 0.3% A187 0.5% A200 3.2%.
[0019] The present invention also provides a method for preparing the UV structural adhesive, which comprises: mixing a UV monomer, a photoinitiator, and a compound antioxidant, stirring until the solid is completely dissolved, then adding a photocuring agent and a functional acrylate, stirring until they are completely dispersed, and then adding a coupling agent and gas silicon, stirring until they are completely dispersed.
[0020] The present invention also provides an application of the UV structural adhesive and UV structural adhesive tape in the field of photovoltaic materials.
[0021] Effects of the Invention The present invention solves the yellowing and temperature resistance problems from a chemical perspective based on the raw material properties of the UV structural adhesive. The UV structural adhesive of the present invention uses a heat-resistant resin (epoxy acrylate) to improve the temperature resistance, and at the same time significantly improves the yellowing problem of the UV structural adhesive through a compounded antioxidant. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1The yellowing conditions of the UV structural adhesives of Comparative Examples 1-3 and Example 1 are shown. DETAILED DESCRIPTION
[0023] In order to make the technical solutions and beneficial effects of the present invention more clearly understandable, the following is a detailed description by listing specific embodiments. The drawings are not necessarily drawn to scale, and local features may be enlarged or reduced to more clearly show the details of the local features; unless otherwise defined, the technical and scientific terms used herein have the same meanings as those in the technical field to which this application belongs.
[0024] The raw materials or instruments used in the present invention without indicating the manufacturer are all conventional products that can be purchased from the market. In certain embodiments, the antioxidant of the present invention is purchased from Tianjin Lianlong Co., Ltd.
[0025] The invention provides a heat-resistant and yellowing-resistant UV structural adhesive. The raw materials for preparing the UV structural adhesive include functional acrylate and compound antioxidant, wherein the compound antioxidant includes a main antioxidant and an auxiliary antioxidant.
[0026] In certain embodiments, the mass ratio of the primary antioxidant to the secondary antioxidant is 1:2 to 2:1; In certain embodiments, the mass ratio of the primary antioxidant to the secondary antioxidant is 1:2, or 1:1.9, or 1:1.8, or 1:1.7, or 1:1.6, or 1:1.5, or 1:1.4, or 1:1.3, or 1:1.2, or 1:1.1, or 1:1, or 1.1:1, or 1.2:1, or 1.3:1, or 1.4:1, or 1.5:1, or 1.6:1, or 1.7:1, or 1.8:1, or 1.9:1, or 2:1.
[0027] In certain embodiments, the mass ratio of the primary antioxidant to the secondary antioxidant is 1:1.
[0028] In certain embodiments, the primary antioxidant is selected from one or more of 1010, 1071, and BHT.
[0029] In certain embodiments, the primary antioxidant is 1010.
[0030] In certain embodiments, the primary antioxidant is 1071.
[0031] In certain embodiments, the primary antioxidant is BHT.
[0032] In certain embodiments, the secondary antioxidant is selected from one or more of 168, 626.
[0033] In certain embodiments, the secondary antioxidant is 168.
[0034] In certain embodiments, the secondary antioxidant is 626.
[0035] In certain embodiments, the compound antioxidant is 1010 and 168.
[0036] In certain embodiments, the compound antioxidant is 1010 and 626.
[0037] In certain embodiments, the compound antioxidant is 1071 and 168.
[0038] In certain embodiments, the compound antioxidant is 1071 and 626.
[0039] In certain embodiments, the compound antioxidant is BHT and 168.
[0040] In certain embodiments, the compound antioxidant is BHT and 626.
[0041] In certain embodiments, the functional acrylate is selected from one or more of epoxy acrylate and multifunctional polyurethane acrylate.
[0042] In certain embodiments, the functional acrylate is epoxy acrylate and multifunctional urethane acrylate.
[0043] In certain embodiments, the functional acrylate is epoxy acrylate.
[0044] In certain embodiments, the functional acrylate is a multifunctional polyurethane acrylate.
[0045] In certain embodiments, the epoxy acrylate is CN104 NS and / or CNUVE151 NS.
[0046] In certain embodiments, the epoxy acrylate is CN104 NS and CNUVE151 NS.
[0047] In certain embodiments, the epoxy acrylate is CN104 NS.
[0048] In certain embodiments, the epoxy acrylate is CNUVE151 NS.
[0049] In certain embodiments, the multifunctional polyurethane acrylate is selected from one or more of HP6612, HP6617, and HP6400.
[0050] In certain embodiments, the multifunctional polyurethane acrylate is HP6612, HP6617, and HP6400.
[0051] In certain embodiments, the multifunctional polyurethane acrylate is HP6612 and HP6617.
[0052] In certain embodiments, the multifunctional polyurethane acrylate is HP6612 and HP6400.
[0053] In certain embodiments, the multifunctional polyurethane acrylate is HP6617 and HP6400.
[0054] In certain embodiments, the multifunctional polyurethane acrylate is HP6612.
[0055] In certain embodiments, the multifunctional polyurethane acrylate is HP6617.
[0056] In certain embodiments, the multifunctional polyurethane acrylate is HP6400.
[0057] In certain embodiments, the functional acrylate is CN104 NS, CNUVE151 NS, HP6612, HP6617, and HP6400.
[0058] In certain embodiments, the functional acrylate is CN104 NS, CNUVE151 NS, HP6612, and HP6617.
[0059] In certain embodiments, the functional acrylate is CN104 NS, CNUVE151 NS, HP6612, and HP6400.
[0060] In certain embodiments, the functional acrylate is CN104 NS, CNUVE151 NS, HP6617, and HP6400.
[0061] In certain embodiments, the functional acrylate is CN104 NS, HP6612, HP6617, and HP6400.
[0062] In certain embodiments, the functional acrylate is CNUVE151 NS, HP6612, HP6617, and HP6400.
[0063] In certain embodiments, the functional acrylate is CN104 NS, CNUVE151 NS, or HP6612.
[0064] In certain embodiments, the functional acrylate is CN104 NS, CNUVE151 NS, or HP6617.
[0065] In certain embodiments, the functional acrylate is CN104 NS, CNUVE151 NS, or HP6400.
[0066] In certain embodiments, the functional acrylate is CN104 NS, HP6612, and HP6617.
[0067] In certain embodiments, the functional acrylate is CN104 NS, HP6612, and HP6400.
[0068] In certain embodiments, the functional acrylate is CN104 NS, HP6617, and HP6400.
[0069] In certain embodiments, the functional acrylate is CNUVE151 NS, HP6612, and HP6617.
[0070] In certain embodiments, the functional acrylate is CNUVE151 NS, HP6612, and HP6400.
[0071] In certain embodiments, the functional acrylate is CNUVE151 NS, HP6617, and HP6400.
[0072] In certain embodiments, the functional acrylate is HP6612 NS, HP6617, and HP6400.
[0073] In certain embodiments, the functional acrylate is CN104 NS and CNUVE151 NS.
[0074] In certain embodiments, the functional acrylate is CN104 NS and HP6612.
[0075] In certain embodiments, the functional acrylates are CN104 NS and HP6617.
[0076] In certain embodiments, the functional acrylate is CN104 NS and HP6400.
[0077] In certain embodiments, the functional acrylate is CNUVE151 NS and HP6612.
[0078] In certain embodiments, the functional acrylate is CNUVE151 NS and HP6617.
[0079] In certain embodiments, the functional acrylate is CNUVE151 NS and HP6400.
[0080] In certain embodiments, the functional acrylate is HP6612 and HP6617.
[0081] In certain embodiments, the functional acrylate is HP6612 and HP6400.
[0082] In certain embodiments, the functional acrylate is HP6617 and HP6400.
[0083] In certain embodiments, the functional acrylate is CN104 NS.
[0084] In certain embodiments, the functional acrylate is CNUVE151 NS.
[0085] In certain embodiments, the functional acrylate is HP6612.
[0086] In certain embodiments, the functional acrylate is HP6617.
[0087] In certain embodiments, the functional acrylate is HP6400.
[0088] In certain embodiments, the raw materials for preparing the UV structural adhesive further include: UV monomer, photoinitiator, photocuring agent, coupling agent, and gas silicone.
[0089] In certain embodiments, the raw materials for preparing the UV structural adhesive are composed of UV monomers, photoinitiators, photocuring agents, functional acrylates, compounded antioxidants, coupling agents, and gas silicones.
[0090] In certain embodiments, the raw materials for preparing the UV structural adhesive include, by weight: UV monomer 40~50% Photoinitiator 1~10% Light curing agent 30~40% Functional acrylate 5~15% Compound antioxidant 0.1~1% Coupling agent 0.1~1% Gas silicon 1~5%.
[0091] In certain embodiments, the raw materials for preparing the UV structural adhesive include 40%, or 40.5%, or 41%, or 41.5%, or 42%, or 42.5%, or 43%, or 43.5%, or 44%, or 44.5%, or 45%, or 45.5%, or 46%, or 46.5%, or 47%, or 47.5%, or 48%, or 48.5%, or 49%, or 49.5%, or 50% of UV monomer, by weight.
[0092] In some embodiments, the raw materials for preparing the UV structural adhesive include 1%, or 1.5%, or 2%, or 2.5%, or 3%, or 3.5%, or 4%, or 4.5%, or 5%, or 5.5%, or 6%, or 6.5%, or 7%, or 7.5%, or 8%, or 8.5%, or 9%, or 9.5%, or 10% of the photoinitiator by weight.
[0093] In certain embodiments, the raw materials for preparing the UV structural adhesive include 30%, or 30.5%, or 31%, or 31.5%, or 32%, or 32.5%, or 33%, or 33.5%, or 34%, or 34.5%, or 35%, or 35.2%, or 35.5%, or 36%, or 36.5%, or 37%, or 37.5%, or 38%, or 38.5%, or 39%, or 39.5%, or 40% of the photocuring agent, by weight.
[0094] In certain embodiments, the raw materials for preparing the UV structural adhesive include, by weight, functional acrylate or 5%, or 5.5%, or 6%, or 6.5%, or 7%, or 7.5%, or 8%, or 8.5%, or 9%, or 9.5%, or 10%, or 10.5%, or 11%, or 11.5%, or 12%, or 12.5%, or 13%, or 13.5%, or 14%, or 14.5%, or 15%.
[0095] In certain embodiments, the raw materials for preparing the UV structural adhesive include 0.1%, or 0.15%, or 0.2%, or 0.25%, or 0.3%, or 0.35%, or 0.4%, or 0.45%, or 0.5%, or 0.55%, or 0.6%, or 0.65%, or 0.7%, or 0.75%, or 0.8%, or 0.85%, or 0.9%, or 0.95%, or 1% of the compound antioxidant, by weight.
[0096] In certain embodiments, the raw materials for preparing the UV structural adhesive include, by weight, 0.1%, or 0.15%, or 0.2%, or 0.25%, or 0.3%, or 0.35%, or 0.4%, or 0.45%, or 0.5%, or 0.55%, or 0.6%, or 0.65%, or 0.7%, or 0.75%, or 0.8%, or 0.85%, or 0.9%, or 0.95%, or 1% of the coupling agent.
[0097] In some embodiments, the raw materials for preparing the UV structural adhesive include 1%, or 1.1%, or 1.2%, or 1.3%, or 1.4%, or 1.5%, or 1.6%, or 1.7%, or 1.8%, or 1.9%, or 2%, or 2.1%, or 2.2%, or 2.3%, or 2.4%, or 2.5%, or 2.6%, or 2.7%, or 2.8%, or 2.9%, or 3%, or 3.1%, or 3.2%, or 3.3%, or 3.4%, or 3.5%, or 3.6%, or 3.7%, or 3.8%, or 3.9%, or 4%, or 4.1%, or 4.2%, or 4.3%, or 4.4%, or 4.5%, or 4.6%, or 4.7%, or 4.8%, or 4.9%, or 5% of gas silica.
[0098] In certain embodiments, the raw materials for preparing the UV structural adhesive are composed of the following components in parts by weight: UV monomer 45.5% Photoinitiator 4% Light curing agent 35.2% Functional acrylate 11% Compound antioxidant 0.6% Coupling agent 0.5% Gas silicon 3.2%.
[0099] In certain embodiments, the UV monomer is IBOA.
[0100] In certain embodiments, the UV monomer is SR506.
[0101] In certain embodiments, the photoinitiator is a UV photoinitiator.
[0102] In certain embodiments, the photoinitiator is selected from one or more of 184D and TPO.
[0103] In certain embodiments, the photoinitiators are 184D and TPO.
[0104] In certain embodiments, the photoinitiator is 184D.
[0105] In certain embodiments, the photoinitiator is TPO.
[0106] In certain embodiments, the photocuring agent is polyurethane acrylate.
[0107] In certain embodiments, the photocuring agent is CR91582.
[0108] In certain embodiments, the coupling agent is a siloxane coupling agent.
[0109] In certain embodiments, the coupling agent is A187.
[0110] In certain embodiments, the fumed silica is hydrophilic fumed silica.
[0111] In certain embodiments, the gas silicon is A200.
[0112] In certain embodiments, the raw materials for preparing the UV structural adhesive are composed of the following components in parts by weight: SR506 45.5% 184D 2% TPO 2% CR91582 35.2% HP6612 11% 1010 0.3% 168 0.3% A187 0.5% A200 3.2%.
[0113] The present invention also provides a method for preparing the UV structural adhesive, which comprises: mixing a UV monomer, a photoinitiator, and a compound antioxidant, stirring until the solid is completely dissolved, then adding a photocuring agent and a functional acrylate, stirring until they are completely dispersed, and then adding a coupling agent and gas silicon, stirring until they are completely dispersed.
[0114] In certain embodiments, the stirring speed is 1000-3000 rpm.
[0115] In certain embodiments, the stirring speed is 1000 rpm, or 1100 rpm, or 1200 rpm, or 1300 rpm, or 1400 rpm, or 1500 rpm, or 1600 rpm, or 1700 rpm, or 1800 rpm, or 1900 rpm, or 2000 rpm, or 2100 rpm, or 2200 rpm, or 2300 rpm, or 2400 rpm, or 2500 rpm, or 2600 rpm, or 2700 rpm, or 2800 rpm, or 2900 rpm, or 3000 rpm.
[0116] In certain embodiments, the stirring speed is 2000 rpm.
[0117] In certain embodiments, after adding the coupling agent and the gas silicon, they are first stirred manually until the gas silicon is dispersed in the system, and then stirred at 2000 rpm until it is completely dispersed.
[0118] In certain embodiments, the glass transition temperature (Tg) of the UV structural adhesive is 90-110°C.
[0119] In certain embodiments, the glass transition temperature (Tg) of the UV structural adhesive is 90°C, or 91°C, or 92°C, or 93°C, or 94°C, or 95°C, or 96°C, or 97°C, or 98°C, or 99°C, or 100°C, or 101°C, or 102°C, or 103°C, or 104°C, or 104.8°C, or 105°C, or 106°C, or 107°C, or 108°C, or 109°C, or 110°C.
[0120] In certain embodiments, the yellowness index (200° C.*3h) of the UV structural adhesive is 1-5.
[0121] In certain embodiments, the yellowness index (200°C*3h) of the UV structural adhesive is 1, or 1.1, or 1.2, or 1.3, or 1.4, or 1.5, or 1.6, or 1.7, or 1.8, or 1.9, or 2, or 2.1, or 2.2, or 2.3, or 2.4, or 2.5, or 2.6, or 2.7, or 2.8, or 2.9, or 3, or 3.1, or 3.2, or 3.3, or 3.4, or 3.5, or 3.6, or 3.7, or 3.8, or 3.9, or 4, or 4.1, or 4.2, or 4.3, or 4.4, or 4.5, or 4.6, or 4.7, or 4.8, or 4.9, or 5.
[0122] The present invention also provides an application of the UV structural adhesive in the field of photovoltaic materials.
[0123] Comparative Example 1: UV structural adhesive without adding heat-resistant resin and compound antioxidant
[0124] The specific formula is shown in Table 1. Monomer IBOA (Sartomer SR506), photoinitiator 184D (Shanghai Guangyi), photoinitiator TPO (Shanghai Guangyi) and antioxidant 1010 (Lianlong) were added in proportion by mass, and the stirring speed was 2000rpm. Stirring was carried out until all solids were dissolved. Then polyurethane acrylate CR91582 (Guangzhou Haohui) was added at a stirring speed of 2000rpm until completely dispersed. Then A187 (Maitu) and gas silicone A200 (Evonik) were added. First, stir manually until the gas silicone was dispersed in the system, and then stir at 2000rpm until completely dispersed. Vacuum degassing and packaging were carried out to test the performance.
[0125] Table 1: UV structural adhesive formula ratio
[0126] Comparative Example 2: UV structural adhesive with epoxy acrylate added but no compound antioxidant added
[0127] The specific formula is shown in Table 1. Monomer IBOA (Sartomer SR506), photoinitiator 184D (Shanghai Guangyi), photoinitiator TPO (Shanghai Guangyi) and antioxidant 1010 (Lianlong) were added in proportion, and the stirring speed was 2000rpm. Stirring was carried out until all solids were dissolved, and then polyurethane acrylate CR91582 (Guangzhou Haohui) and epoxy acrylate CN104 (Sartomer) were added. Stirring speed was 2000rpm. Stirring was carried out until they were completely dispersed. Then A187 (Maitu) and gas silicone A200 (Evonik) were added. First, stir manually until the gas silicone was dispersed in the system, and then stir at 2000rpm until it was completely dispersed. Vacuum degassing and packaging were carried out, and the performance was tested.
[0128] Comparative Example 3: UV structural adhesive with multifunctional polyurethane acrylate and no compound antioxidant The specific formula is shown in Table 1. Monomer IBOA (Sartomer SR506), photoinitiator 184D (Shanghai Guangyi), photoinitiator TPO (Shanghai Guangyi) and antioxidant 1010 (Lianlong) were added in proportion, and the stirring speed was 2000rpm. Stirring was carried out until all solids were dissolved. Then, polyurethane acrylate CR91582 (Guangzhou Haohui) and multifunctional polyurethane acrylate 6617 (Guangzhou Haohui) were added. Stirring speed was 2000rpm. Stirring was carried out until they were completely dispersed. Then A187 (Maitu) and gas silicone A200 (Evonik) were added. First, stir manually until the gas silicone was dispersed in the system, and then stir at 2000rpm until it was completely dispersed. Vacuum degassing and packaging were carried out to test the performance.
[0129] Comparative Example 4: UV structural adhesive with multifunctional polyurethane acrylate and increased amount of antioxidant The specific formula is shown in Table 1. Monomer IBOA (Sartomer SR506), photoinitiator 184D (Shanghai Guangyi), photoinitiator TPO (Shanghai Guangyi), primary antioxidant 1010 (Lianlong), and secondary antioxidant 168 (Lianlong) were added in proportion, and the stirring speed was 2000rpm. Stirring was carried out until all solids were dissolved, and then polyurethane acrylate CR91582 (Guangzhou Haohui) and multifunctional polyurethane acrylate 6617 (Guangzhou Haohui) were added. Stirring speed was 2000rpm. Stirring was carried out until completely dispersed, and then A187 (Maitu) and gas silicone A200 (Evonik) were added. First, stir manually until the gas silicone was dispersed in the system, and then stir at 2000rpm until completely dispersed. Vacuum degassing and packaging were carried out, and the performance was tested.
[0130] Example 1: UV structural adhesive with multifunctional polyurethane acrylate and compound antioxidant The specific formula is shown in Table 1. Monomer IBOA (Sartomer SR506), photoinitiator 184D (Shanghai Guangyi), photoinitiator TPO (Shanghai Guangyi), primary antioxidant 1010 (Lianlong), and secondary antioxidant 168 (Lianlong) were added in proportion, and the stirring speed was 2000rpm. Stirring was carried out until all solids were dissolved, and then polyurethane acrylate CR91582 (Guangzhou Haohui) and multifunctional polyurethane acrylate 6617 (Guangzhou Haohui) were added. Stirring speed was 2000rpm. Stirring was carried out until completely dispersed, and then A187 (Maitu) and gas silicone A200 (Evonik) were added. First, stir manually until the gas silicone was dispersed in the system, and then stir at 2000rpm until completely dispersed. Vacuum degassing and packaging were carried out, and the performance was tested.
[0131] Example 2: UV structural adhesive performance test Yellowing test: Take an appropriate amount of glue and cure it into a 400-450μm sheet with a curing energy of 3000mJ / cm 2 , put it in a 200℃ oven for 3h, take it out and cool it down. Figure 1 The yellowing test was conducted using a colorimeter LS155 (Linshang Technology) according to ASTM E313. The test results are shown in Table 2.
[0132] Glass transition temperature: Take an appropriate amount of glue and solidify it into a 400-450μm sheet, with a curing energy of 3000mJ / cm 2 , TMA test was carried out to obtain the glass transition temperature. The results are shown in Table 2.
[0133] Table 2: UV structural adhesive performance test results
[0134] The results show that the glass transition temperature of the UV structural adhesive without adding heat-resistant resin (Comparative Example 1) is too low and the heat resistance is poor; the UV structural adhesive without adding compound antioxidant (Comparative Examples 1-3) has a high degree of yellowing. The UV structural adhesive with multifunctional polyurethane acrylate and compound antioxidant (Example 1) has a high glass transition temperature and a low degree of yellowing, which meets the performance requirements of the field for UV structural adhesives.
[0135] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.
Claims
1. A heat-resistant and yellowing-resistant UV structural adhesive, characterized in that: The raw materials for preparing the UV structural adhesive include: functional acrylate and compound antioxidant, wherein the compound antioxidant includes a main antioxidant and an auxiliary antioxidant.
2. The UV structural adhesive according to claim 1, characterized in that: The mass ratio of the primary antioxidant to the secondary antioxidant is 1:2 to 2:1; And / or, the primary antioxidant is selected from one or more of 1010, 1071, and BHT; And / or, the secondary antioxidant is selected from one or more of 168, 626.
3. The UV structural adhesive according to claim 2, characterized in that: The mass ratio of the primary antioxidant to the secondary antioxidant is 1:1; And / or, the primary antioxidant is 1010; And / or, the secondary antioxidant is 168.
4. The UV structural adhesive according to claim 1, characterized in that: The functional acrylate is selected from one or more of epoxy acrylate and multifunctional polyurethane acrylate; And / or, the epoxy acrylate is CN104 NS and / or CNUVE151 NS; And / or, the multifunctional polyurethane acrylate is selected from one or more of HP6612, HP6617, and HP6400.
5. The UV structural adhesive according to claim 1, characterized in that: The raw materials for preparing the UV structural adhesive also include: UV monomer, photoinitiator, photocuring agent, coupling agent, and gas silicon; And / or, in parts by weight, the raw materials for preparing the UV structural adhesive include: UV monomer 40~50% Photoinitiator 1~10% Light curing agent 30~40% Functional acrylate 5~15% Compound antioxidant 0.1~1% Coupling agent 0.1~1% Gas silicon 1~5%.
6. The UV structural adhesive according to claim 5, characterized in that: The raw materials for preparing the UV structural adhesive are composed of the following components in parts by weight: UV monomer 45.5% Photoinitiator 4% Light curing agent 35.2% Functional acrylate 11% Compound antioxidant 0.6% Coupling agent 0.5% Gas silicon 3.2%.
7. The UV structural adhesive according to claim 6, characterized in that: The UV monomer is IBOA; And / or, the photoinitiator is an ultraviolet photoinitiator; And / or, the photocuring agent is polyurethane acrylate; And / or, the coupling agent is a siloxane coupling agent; And / or, the fumed silica is hydrophilic fumed silica.
8. The UV structural adhesive according to claim 7, characterized in that: The UV monomer is SR506; And / or, the photoinitiator is 184D and TPO; And / or, the light curing agent is CR91582; And / or, the coupling agent is A187; And / or, the gas silicon is A200; And / or, in parts by weight, the raw materials for preparing the UV structural adhesive consist of the following components: SR506 45.5% 184D 2% TPO 2% CR91582 35.2% HP6612 11% 1010 0.3% 168 0.3% A187 0.5% A200 3.2%。 9. A method for preparing a UV structural adhesive according to any one of claims 1 to 8, characterized in that: The method comprises: mixing UV monomer, photoinitiator and compound antioxidant, stirring until solid is completely dissolved, adding photocuring agent and functional acrylate, stirring until completely dispersed, adding coupling agent and gas silicon, stirring until completely dispersed.
10. Use of the UV structural adhesive according to any one of claims 1 to 8 in the field of photovoltaic materials.
Citation Information
Patent Citations
High-thixotropy high-temperature-resistant yellowing-resistant photovoltaic solder strip UV adhesive, preparation method and sizing method
CN117384580A
Light-curing edge sealing adhesive
CN103865470A
Acrylic acid adhesive emulsion for OCA optically clear adhesive film and preparation method thereof
CN105440995A
Photo-thermal dual-curing resin composition as well as preparation method and application thereof
CN113652186A
Yellowing-resistant self-decoloration UV resin and application thereof in UV glue dripping
CN114015013A